2022
DOI: 10.1111/1556-4029.15038
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic femicide: The influence of psychopathy on intimate partner homicide

Abstract: High scores in psychopathy were associated with acts of violence, and the prevalence of this condition is greater among the prison population than among the general population.In terms of its relation to femicide, two studies, one carried out in Sweden and another in Spain with a prison population, found that psychopathy is an uncommon condition among perpetrators of femicide. This study analyzes 97 cases of femicide in the whole of Spain, in which it was possible to evaluate the degree of psychopathy of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
1
4
0
2
Order By: Relevance
“…A similar result was reported by Santos et al. (2022). It has been established empirically that MD offenders have a propensity to commit FMF instead of IPF or in conjunction with IPF, and this trend was observed with the NI sample (Oram et al., 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A similar result was reported by Santos et al. (2022). It has been established empirically that MD offenders have a propensity to commit FMF instead of IPF or in conjunction with IPF, and this trend was observed with the NI sample (Oram et al., 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Belfrage and Rying (2004) suggest femicide offenders are four times more likely to also commit suicide compared to homicides that do not focus on women. Also, Solinas‐Saunders (2022) compared the sociodemographic and contextual factors related to all 153 FS and 186 IPF recorded in Italy from 2015 to 2019 and found that perpetrators of FS were more likely to murder multiple victims and less likely to have any violent criminal convictions prior to the offence compared to IPF offenders.…”
Section: Femicidementioning
confidence: 99%
“…The instrument used to obtain the data of interest was a semistructured interview designed by the National Team for the Detailed Review of Gender Homicides of the Secretary of State for Security of Spanish Ministry of the Interior (González-Álvarez, Garrido, et al, 2018;Santos-Hermoso, González-Álvarez, López-Ossorio, et al, 2022;Santos-Hermoso et al, 2021). Two interview models were used, but with the same type of questions, one for women victims of IPVAW and another for people close to the victims of IPHAW to elaborate a psychological autopsy (research methodology to improve knowledge in cases of IPHAW; McPhedran et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Global, European, and Italian data all indicate that most female homicide victims are killed by intimate partners or family members [ 4 , 7 ]. Many possible explanations have been suggested for this finding, with most focusing on the psychopathological, sociological, and criminological perspectives on the phenomenon [ 8 , 9 , 10 , 11 , 12 , 13 ]. Gender inequality is considered the most important factor influencing gender-based violence; therefore, it is recognized as a significant aspect of intimate partner homicide.…”
Section: Introductionmentioning
confidence: 99%